Years of life lost from ischaemic and haemorrhagic stroke related to ambient nitrogen dioxide exposure: A multicity study in China - Li, Jie (Ecotoxicol Environ Saf, 2020)
Few multicity studies have been conducted in developing countries to distinguish the acute effects of ambient nitrogen dioxide (NO(2)) on the years of life lost (YLL) from different subtypes of stroke. We aimed to differentiate the associations between NO(2) exposure and YLL from major pathological types of stroke in China, and estimate the relevant economic loss. A time-series study was conducted to explore the associations between short-term NO(2) exposure and YLL from ischaemic and haemorrhagic stroke from 2013 to 2017 in 48 Chinese cities. Daily NO(2) data and stroke mortality counts for each city were obtained from the National Urban Air Quality Real-time Publishing Platform and Chinese Center for Disease Control and Prevention, respectively. Generalized additive models were applied to estimate the cumulative effects of NO(2) in each city, and meta-analysis was used to combine the city-specific estimates. The relevant economic loss was estimated using the method of the value per statistical life year (VSLY). A 10 μg/m(3) increase in ambient NO(2) concentration on the present day and previous day (lag 0–1) would lead to relatively higher increments in percentage change of YLL from ischaemic stroke (0.82%, 95% CI: 0.46%, 1.19%) than haemorrhagic stroke (0.46%, 95% CI: 0.09%, 0.84%). The association was significantly stronger in the low-education population than high-education population for ischaemic stroke. Furthermore, significantly higher association was found in South China than those in North China for both subtypes of stroke. Economic loss due to excess YLL from ischaemic stroke related to NO(2) exposure was higher than that for haemorrhagic stroke. Our study indicated higher association and economic loss of ischaemic than haemorrhagic stroke related to NO(2) exposure in China, which informed priorities for type-specific stroke prevention strategies related to NO(2) pollution and vulnerable population protection.